ODONTEKTOMI, TATALAKSANA GIGI BUNGSU IMPAKSI - Rahayu, Sri (E-Journal Widya Kesehatan dan Lingkungan, 2018)
Odontectomy or the surgical removal of teeth is the most frequent surgery in daily practice of Oral surgery Specialists. In the process of the emergence of the third molars or wisdom teeth as the last teeth to erupt into the oral cavity, which is usually difficult to erupt or impacted. The purpose of this paper is to discuss: (1) the teeth impaction, (2). the benefits and risks of Tooth impaction that may arise. The method used is library research with descriptive, explorative approaches. It can be concluded that: (1) the dental impaction either in part or in whole/partial/total, each of which can cause serious problems and potentially cause mild to severe complications and even life-threatening, (2) the surgical removal of teeth with or without odontectomy, should be determined per the case along with the patient. It is compulsory to remind to fellow Specialist oral surgery to give a description of the benefits and risks that may arise in Odontectomy or the surgical removal of teeth and and determine a case by case with patients. It is in accordance with the recommendation of the American Association of Oral and Maxillofacial Surgeons (AAOMS).